Interaction between the West African Monsoon and the summer Mediterranean climate: An overview. - (:unkn) unknown (My University, 2013)
Although in the framework of the global climate research the Mediterranean climate variability andthe West African Monsoon (WAM) dynamics have been considered for a long time as “passive”systems, i.e., prone to the influence of large scale ocean and atmospheric variability, over the lastdecade many studies have been dedicated to the WAM-Mediterranean interaction and the active roleof these climate systems has been highlighted. This article presents the WAM-Mediterraneanteleconnection through an overview of the recent literature, describing the observational evidencesand the dynamical mechanisms underlying this climate teleconnection. The influence of the MediterraneanSea thermal anomalies on the WAM dynamics has been robustly demonstrated, and aWAM modulation of the atmospheric circulation over the Euro-Atlantic sector has been highlighted.On the other hand, the direct effects of the WAM dynamics on the Mediterranean climate still needto be more clearly understood.
Keywords: African Research